1990
DOI: 10.2186/jjps.34.340
|View full text |Cite
|
Sign up to set email alerts
|

The balance of occlusal contacts during intercuspation using T-Scan system.

Abstract: Many methods have been clinically applied for the occlusal analysis in the intercuspal position. However, none of these methods are quantitative. This study described the new software version of the T-Scan system to record and analyze occlusal contact balance in the anterior-posterior and right-left directions. Six time moment statistics and five force moment statistics were calculated in the midsagittal and the incisal axes of the occlusal plane. In the present study, informed consent was obtained from 60 sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

1995
1995
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…In T-scan system analysis of occlusion in 93 normal subjects, Maness and Podoloff (1989) found that the normal dentition was bisymmetrical to the sagittal plane and described that the anteroposterior dynamic center of tooth contact was located at the first molar. Nabeshima et al(1990) also studied occlusion in 90 normal subjects using the T-scan system and obtained similar findings. Analysis of the postoperative occlusion in the patients with mandibular fracture treated by our method produced similar results as those reported by Maness and Podoloff (1989) and Nabeshima et al (1990).…”
Section: Review Of Patientsmentioning
confidence: 59%
See 1 more Smart Citation
“…In T-scan system analysis of occlusion in 93 normal subjects, Maness and Podoloff (1989) found that the normal dentition was bisymmetrical to the sagittal plane and described that the anteroposterior dynamic center of tooth contact was located at the first molar. Nabeshima et al(1990) also studied occlusion in 90 normal subjects using the T-scan system and obtained similar findings. Analysis of the postoperative occlusion in the patients with mandibular fracture treated by our method produced similar results as those reported by Maness and Podoloff (1989) and Nabeshima et al (1990).…”
Section: Review Of Patientsmentioning
confidence: 59%
“…Nabeshima et al(1990) also studied occlusion in 90 normal subjects using the T-scan system and obtained similar findings. Analysis of the postoperative occlusion in the patients with mandibular fracture treated by our method produced similar results as those reported by Maness and Podoloff (1989) and Nabeshima et al (1990).…”
Section: Review Of Patientsmentioning
confidence: 59%
“…1 Usually, the occlusal contact area of the first permanent molars is the largest in the whole dentition in a healthy population. 2 And the maximum occlusal force tolerated by the periodontal tissue is also greatest in the first permanent molar. However, abnormal occlusal contact relationships and excessive occlusal forces can alter the state of periodontal support tissues and promote the development of periodontitis.…”
Section: Introductionmentioning
confidence: 99%
“…Yurkstas proposed in his study half a century ago that occlusal contact exists between the maxillary and mandibular teeth and that contact between the upper and lower teeth is the most extensive and homogeneous in the intercuspal position 1 . Usually, the occlusal contact area of the first permanent molars is the largest in the whole dentition in a healthy population 2 . And the maximum occlusal force tolerated by the periodontal tissue is also greatest in the first permanent molar.…”
Section: Introductionmentioning
confidence: 99%
“…We can use the T-Scan system during the treatment with a complete removable denture to analyze and measure occlusal forces, and with the computer-guided corrective adjustments, the occlusal balance can measurably improve [9,10].…”
Section: Introductionmentioning
confidence: 99%